ATRIBUTOS FÍSICOS DO SOLO SOB DIFERENTES TIPOS DE MANEJO - SANTOS JUNIOR, Benedito Amauri dos; FALCÃO, Karina dos Santos2; MENEZES, Rafael da Silva; MONTEIRO, Felipe das Neves; SIMÕES, Mayara dos Santos (ANAIS DO ENIC, 2022)
-